(untitled) (Semiárida, 2019)
The main source of fluoride in superficial or groundwater is the solubilization of fluorinated mineral compounds. Although it is an oligonutrient, its excess can be toxic to organisms. In La Pampa there is information about its concentrations in groundwater, the main source of many cities and towns. The information referred to superficial waters is scarce, which makes it difficult to estimate their possible effects on aquatic organisms. The objective was to know the fluoride concentrations in pampean aquatic ecosystems and analyze if they are superior to the guide levels for biota protection. Samples were taken between 2002 and 2017 in 27 aquatic ecosystems. Flouride determinations were made with the SPANDS colorimetric method. Concentrations varied between 0.2 and 13.89 mg.L-1 and exceeded the national guideline for aquatic biota protection (1.4 mg.L-1) in 22 ecosystems. There was a correlation with salinity, since higher concentrations were registered in saline shallow lakes. No regional distribution pattern was detected but the highest concentrations (>9 mg.L-1) were recorded in northern lakes. The values of La Pampa, slightly higher than those of most of the water bodies in the province of Buenos Aires, were similar to those of Chasicó Lake, in the southwest of that province.